Effect of Sodium Sesquicarbonate Supplementation on Blood Biochemical parameters and Antioxidant activity in Lactating Karan Fries Cattle - Sharma, Hunny (Indian Journal of Animal Nutrition, 2020)
In the present research, the impact of sodium sesquicarbonate (NaSC) on the biochemical parameters of the blood and the function of antioxidant enzymes in lactating crossbred cattle were examined. At the start of the experiment, 24 lactating crossbred cattle randomly distributed in four groups, namely Control, T1, T2 and T3 on the basis of milk yield, body weight, parity and days in milk, were supplemented with NaSC @ 0, 1, 1.5 and 2 percent of DMI for 120 days respectively. Under similar environmental conditions, all the groups were maintained and feeding was done as per ICAR (2013). Blood samples were obtained initially at 0 days and then for biochemical parameters at the monthly interval. The antioxidant function of blood hemolysate was measured at monthly intervals after feeding. The results of the experiment showed that sodium sesquicarbonate supplementation appeared to increase plasma glucose, but no substantial difference was discovered by statistical data analysis. Antioxidative enzymatic activity was in the normal physiological range which indicates that buffer supplementation had no detrimental effect on animal’s health.